The Unpublished Correspondence between Hans Simmel and Max Horkheimer (1936–1943). Some Remarks on Critical Theory, Georg Simmel’s Sociology, and the Tasks of the Institute for Social Research - Ruggeri, Davide (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2020)
The focus of analysis is the reconstruction of the relationship between the philosopher and sociologist Max Horkheimer (1895–1973) and Hans Simmel (1891–1943), Georg Simmel’s first son. Its basis is an unpublished folder at the Universitätsarchiv, Frankfurt am Main. Under review is the attempt by Horkheimer to arrange a visa for Hans Simmel to travel to the US. On the one hand, a testimony is revealed of an intellectual debt (Horkheimer’s to Georg Simmel), which was transformed into a biographical debt toward Hans; on the other hand, we sketch a tragic link with the rise of the Nazi party and the consequences of the persecution and diaspora of Jews from Germany, as well as the Institute for Social Research (New York) commitments to help German intellectuals. Consequently, there are two principal aims: firstly, to reconstruct the biographical events which connect Hans Simmel and Max Horkheimer at a specific period (1936–1943), furnishing details about concrete aspects of their historical situation; secondly, in the background we examine the ambivalent relationship between Georg Simmel’s thought and the former Frankfurt School authors, who appreciated Simmel’s innovative style, yet distanced themselves from his irrational-bourgeois approach (due to the stigmatization of Korsch and Lukács).